Hubungan antara Konsentrasi Minyak Atsiri Kayu Manis (Cinnamomum burmannii Nees Ex Bl.) dalam Lotion dengan Sifat Fisik dan Tingkat Kesukaan Konsumen - Erwan Kurnianto; Nining Sugihartini; Laela Hayu Nurani (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2017)
Essential oil of Cinnamomum burmannii contains cinnamaldehyde as active substance as antibacterial and repellant. The study about development of dosage forms was needed in order be useful to people. The purpose of this study was to determine the concentration’s effect of cinnamon to the physical characteristic and results hedonic test of lotion. This study was done in Laboratory of Pharmacy UAD in 2014 that was begun with distillation of essential oil. Then, it was formulated as lotion with concentration 1% (F1), 3% (F II), 5% (F III), 7% (F IV), respectively. The lotion was evaluated its physical characteristic (homogeneity, viscosity, spreadability, adhesivity, pH) and hedonic test to know the level of acceptability based on colour and flavor of lotion. Data was collected by quistionnaire. Results of study showed that all of the lotion was homogenous. The increasing concentrations of cinnamon caused decreasing of viscosity (p <0.05) and adhesivity (P <0.05), an increasing of spreadability (P <0.05), did not affect the pH value (p> 0.05), and increasing hedonic level until 5% concentration. It can be concluded that concentration of essential oil of cinnamon at 5% fullfilled the requirement of spreadability, adhesivity, pH and the most prefered by consumers.